THE IMPORTANCE OF USING GAMES IN TEACHING VOCABULARY (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
This article is devoted to show the importance of using lexical games in the classroom as they are very effective means of teaching, which allows to make the learning process exciting and interesting. Using games at the lessons helps to create a trusting and relaxed atmosphere and helps to maintain the students' interest in the subject. Games help learners to become creative individuals, teach them to treat any activity with creativity and interest.